DIRECTIONS FOR IMPROVING THE INSTITUTIONAL SUPPORT OF THE STATE POLICY FOR THE DEVELOPMENT OF SMALL BUSINESS IN RURAL AREAS - KRAVCHYK, Yurii; MOSKALYUK, Oleksandr; SHPILEVA, Vira; KUTSENKO, Boris (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The relevance of the problem of formation and implementation of the state policy for the development of small entrepreneurship in rural areas of Ukraine is revealed, in particular in the aspect of improving the institutional support of state policy in this area. The purpose of the study is to substantiate the ways and means of improving the institutional support of the state policy of promoting the development of small entrepreneurship in rural areas. The directions (1 – macro-level, 2 – regional-level) that should be followed to form and implement the policy of small business development in the rural areas of Ukraine have been determined. It is shown that strategic goals in this area should be formed in the context of the economic independence of its subjects, ensuring the appropriate level of economic security and expanded reproduction of the economic and resource potential of enterprises. It was determined that the leading place in the system of state policy measures in the field of small business development in rural areas is assigned to the institutional support of state policy. It is about institutional-legal and institutional-organizational policy. It was established that in the institutional and organizational plan, the measures that should be implemented are: strengthening the programmatic and normative regulation of the development of small entrepreneurship and helping to increase the level of motivation of local self-government bodies regarding the implementation of measures and achieving success in this area. Accordingly, at the regional and local level, it is necessary to: activate the management functions of the authorities in the direction of the formation of a favorable business climate and a safe business environment; improve regulatory policy, eliminate manifestations of monopoly, "client" relations and corruption in "government-business" relations; to strengthen the level of financial support of small private business entities.
Keywords: local economic development; small business; entrepreneurship; regional economy; small business sector; institutional support; development policy; territorial communities